Case studies in sport development : contemporary stories promoting health, peace, and social justice - Schinke, Robert J.; Lidor, Ronnie (Morgantown, WV : Fitness Information Technology, 2013)
Sport is more than competition and the opportunity to become physically fit. Sport and physical activity offer opportunities for people and communities to forge improved relations. Case Studies in Sport Development: Contemporary Stories Promoting Health, Peace, and Social Justice reveals how experiences from across our global community have served as the conduit to harmony within and among people. Internationally renowned co-editors Robert J Schinke and Ronnie Lidor have structured this compilation into three key sections: Remedying Marginalization; Health & Well-Being; Sport for Peace & Social Justice. The international collection of contributing authors to this book speak from the heart about personal yet widely applicable sport and physical activity experiences. These cases provide the reader with hope that sport and physical activity can provide answers to many of todays and tomorrows societal challenges within people and communities, and among countries, races, and religions.
Case studies in sport development : opening up the discussion / Robert J. Schinke and Ronnie Lidor -- Intending to create a landmark will change you / Carole A. Oglesby -- The bridge goes both ways : lessons learned from athletes searching for direction and meaning / William D. Parham -- Run your dream / Hussain Haleem -- Queering sport one team at a time / Barbara Ravel -- From the reserve to the rink : pursuing a hockey dream as an aboriginal athlete / Amy T. Blodgett and Duke Peltier -- Exercising fat control, resistance, and self-compassion : two ethnographic stories from the field / Kerry R. McGannon and Kathi A. Cameron -- Using games to enhance life satisfaction and self worth of orphans, teenagers living in poverty, and ex-gang members in Latin America / Stephanie J. Hanrahan -- Stories from the basement : narratives on disability / Tamar Z. Semerjian -- It takes several northern communities to raise a reflexive and effective sport researcher / Audrey R. Giles -- More than just medals : athletes' storied experiences with sport for development and peace / Erin Cameron, Ann Peel, Marko Begovic, and Scott Sandison -- Fortunate tales of a decent sociologist, a failed footballer, and a reluctant peace maker / John Sugden -- From the laboratory to the field : working with soccer players from conflicting cultures / Ronnie Lidor -- Project Nepal : the experience of implementing life skills programming in a developing country / Tanya Forneris -- The wheels of hope / Yeshayahu Hutzler -- Putting social justice in the game : towards a progressive coaching psychology / Ted M. Butryn -- Cases in sport development : our reflections / Ronnie Lidor and Robert J. Schinke
Keywords: Sports -- Social aspects; Sports -- Health aspects; Sports administration; Sports and state